Analisis Faktor-Faktor yang Mempengaruhi Minat Nasabah dalam Menggunakan Kartu Kredit - Iim Imtihan; ikhwan hasan; Putri Anisak (Universitas Negeri Padang, 2021)
The purpose of this study was to determine the factors that influence customer interest in using a credit card PT. Bank Negara Indonesia Padang. The type of research is descriptive and qualitative research. The sampling technique used is Purposive sampling. The type of data used is primary and secondary data. The data analysis technique used is multiple linear regression by using t test and F test. The results of this study indicate that: (1) advertising has a positive and significant effect on customer interest in using a credit card PT. Bank Negara Indonesia Padang, (2) lifestyle has a positive and significant effect on customer interest in using a credit card PT. Bank Negara Indonesia Padang, (3) customer value has a positive and significant effect on customer interest in using a credit card PT. Bank Negara Indonesia Padang and (4) advertising, lifestyle and customer value have a positive and significant effect on customer interest in using a credit card PT. Bank Negara Indonesia Padang.